LES LIMITES DES IDEES DE LAURENT-DESIRE KABILA POUR LA RECONSTRUCTION DE LA REPUBLIQUE DEMOCRATIQUE DU CONGO - LOFETU, Pierre BOFENDA (IJRDO - Journal of Social Science and Humanities Research, 2021)
During all his reign to the head of the DRC, the worry of Laurent- Désiré Kabila was to lead a fight set against the occupation and the exploitation of his country by the strangers. On the diplomatic plan, he wanted to be independent of big western powers. He came closer a lot of the countries as Cuba, Libya, Sudan, North Korea. He incited the people Congolese to adhere to his vision according to which the state had to be conceived like a collective project. A project that takes into account the real needs of the populations and that privileges the auto-hold in charge. This utopian vision of the state that dreamed Laurent- Désiré Kabila, was fatal for his régime.